A chromosome-level genome assembly of the pollinating fig wasp Valisia javana. (20th May 2022) - Chen, Lianfu; Feng, Chao; Wang, Rong; Nong, Xiaojue; Deng, Xiaoxia; Chen, Xiaoyong; Yu, Hui
Abstract: Fig wasp has always been thought the species-specific pollinator for their host fig (Moraceae, Ficus ) and constitute a model system with its host to study co-evolution and co-speciation. The availability of a high-quality genome will help to further reveal the mechanisms underlying these characteristics. Here, we present a high-quality chromosome-level genome for Valisa javana developed by a combination of PacBio long-read and Illumina short-read. The assembled genome size is 296.34 Mb from 13 contigs with a contig N50 length of 26.76 kb. Comparative genomic analysis revealed expanded and positively selected genes related to biological features that aid fig wasps living in syconium of its highly specific host. Protein-coding genes associated with chemosensory, detoxification and venom genes were identified. Several differentially expressed genes in transcriptome data of V. javana between odor-stimulated samples and the controls have been identified in some olfactory signal transduction pathways, e.g. olfactory transduction, cAMP, cGMP-PKG, Calcim, Ras and Rap1. This study provides a valuable genomic resource for a fig wasp, and sheds insight into further revealing the mechanisms underlying their adaptive traits to their hosts in different places and co-speciation with their host.